Feedback on “Recording of Alcohol Use Disorder in Electronic Health Records: Developing a Recommended Codelist for Research” [Letter] - Wijaya A; Kholidah D; Marselina EV (Clinical Epidemiology)
Avid Wijaya, Diniyah Kholidah, Elystia Vidia Marselina Medical Record and Health Information Department, Poltekkes Kemenkes Malang, Kota Malang, Jawa Timur, IndonesiaCorrespondence: Avid Wijaya, Poltekkes Kemenkes Malang, Jl. Besar Ijen 77C, Malang, Indonesia, Email avidwijaya@poltekkes-malang.ac.id